Glaucoma awareness and access to healthcare: perceptions among glaucoma patients in Tanzania. Issue 1077 (11th June 2015) - Gilmour-White, Jeremy A; Shah, Peter; Cross, Vinette; Makupa, William; Philippin, Heiko
ABSTRACT: Objective: To investigate the barriers to access to eye health services for patients with glaucoma in Tanzania with the aim of identifying key areas for improvement and further research. Design: Qualitative investigation using face-to-face semi-structured interviews with patients recruited from the Kilimanjaro Christian Medical Centre (KCMC) outpatient eye clinic. This project is part of the international strategy of the Research into Glaucoma and Ethnicity (ReGAE) programme. Methods: Interviews were conducted with the help of a translator; all data were transcribed in Swahili and then translated into English. Manual coding and qualitative analysis was used to identify major themes and relevant concepts. Data were collected during May and June 2013. Main outcome measures: Qualitative data on glaucoma awareness and access to healthcare. Results: 12 patients (7 men, 5 women) of mean age 67.5 years (range 53–86 years) were interviewed. All participants had a previous diagnosis of glaucoma and no other eye conditions. The understanding of glaucoma was limited and the capacity for healthcare providers to improve glaucoma knowledge seemed underused. Participants had particular difficulty in understanding the aetiology and chronicity of the disease. Socioeconomic factors also posed significant barriers to service usage. Conclusions: Among many barriers to access to health services for patients with glaucoma, knowledge of the condition was identified as a key issue. Enhancing the understanding of glaucoma may improve access by triggering earlier presentation, informing those at risk and improving adherence to treatment. This is an area for further research with potential for improving service provision.